Collection quality analysis at the Animal Husbandry Library, Universitas Padjadjaran - Riyanto, Slamet; Mayasari, Novi; Hermansyah, Nono; Kusuma, Angga Nata; Ismiraj, Muhammad Rifqi (Jurnal Kajian Informasi dan Perpustakaan, 2023)
The library has the quality in the service in the collection of the library. Enhancing library service quality is paramount to ensure users derive greater satisfaction and value. The Faculty of Animal Husbandry Library, Universitas Padjadjaran, has special collection in the animal husbandry science can access students, lecturer, and staff. The purposes this research knew the collection quality analysis at the Animal Husbandry Library, Universitas Padjadjaran, with analyse of the physical and digital library collections’ at the Faculty of Animal Husbandry Library, Universitas Padjadjaran. The research method used a descriptive quantitative methodology using a survey with 132 participating respondents. The participants comprised students enrolled in the faculty, represented by every academic year, from incoming students to those in their final year. The study procedure encompassed problem identification, questionnaire design, participant selection, questionnaire distribution, and survey data handling. The collected survey data were analyzed descriptively and graphically displayed for simplicity in data interpretation. The survey questions were categorized into four evaluative themes: collection diversity, collection completeness, collection currentness, and collection condition. The outcomes indicated consistent satisfaction from the respondents regarding the evaluated areas. Several recommendations were proposed regarding the physical collection of rare books in sub-optimal conditions. In conclusion, users express satisfaction with the diversity, completeness, timeliness, and condition of both physical and digital collections in the Animal Husbandry Faculty Library, Universitas Padjadjaran. Regular assessment of user satisfaction is necessary as a roadmap for augmenting the quality of library services.